Comparison of the Effects of Reflection and Contemplation Activities on Service-Learners’ Cognitive & Affective Mindfulness - Stewart, Trae; Alrutz, Megan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
This study investigates the extent to which service-learners’ mindfulness is affected by engagement in reflection (e.g., dialogue) and contemplation activities (e.g., labyrinth tracing). The results are compared within and between treatment groups, while covarying for participants’ initial levels of mindfulness. While both dialogue and contemplative labyrinth treatment groups reported increases in mindfulness as measured by CAMS-R, neither within or between group overtime-changes were significant. Contemplative labyrinth tracing as a reflection activity does not appear to be better than dialogue at increasing mindfulness in service-learners. However, contemplative reflection performed as well as traditional dialogue reflection.